2003
DOI: 10.1007/s00198-003-1512-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of physical capacity and quality of life in osteoporotic women

Abstract: Energy expenditure showed a correlation with the angle of thoracic kyphosis. Patients with or without osteoporosis showed the same energy expenditure during the walking period. The SF-36 score was similar for the three groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 18 publications
1
26
0
4
Order By: Relevance
“…Sixteen studies that met all inclusion criteria were included in the final analysis [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] with a total of 3131 men and women (1698 with vertebral fracture, and 1433 without vertebral fracture). Fourteen of these studies were cross-sectional [13-17, 19, 20, 22-28], one case-control [21], and one baseline data from an RCT [18].…”
Section: Description Of Studies Identifiedmentioning
confidence: 99%
See 4 more Smart Citations
“…Sixteen studies that met all inclusion criteria were included in the final analysis [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] with a total of 3131 men and women (1698 with vertebral fracture, and 1433 without vertebral fracture). Fourteen of these studies were cross-sectional [13-17, 19, 20, 22-28], one case-control [21], and one baseline data from an RCT [18].…”
Section: Description Of Studies Identifiedmentioning
confidence: 99%
“…Osteoporosis was defined as T score ≤ 2.5 SD, and lumbar BMD was measured in five studies [19][20][21][22]24], eight studies reported lumbar or/and hip BMD [13, 16-18, 23, 25, 27, 28], and in three studies the site of DXA scan was not mentioned [14,15,26]. Vertebral fractures were identified using Semi-quantitative (SQ) method in 11 studies [13, 16, 17, 21-25, 27, 28], quantitative morphometric (QM) method in two studies [14,19], the SQ, the binary semi quantitative (BSQ), and the QM in one study, the Japanese diagnostic criteria in one study [26], and in one study the method is not mentioned [15]. The number of participants with vertebral fracture in each study ranged from 9 [28] to 548 [17].…”
Section: Description Of Studies Identifiedmentioning
confidence: 99%
See 3 more Smart Citations